2013
DOI: 10.1038/nrneurol.2013.10
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid biomarkers in Parkinson disease

Abstract: Clinical diagnosis of Parkinson disease (PD) is difficult in early stages of disease, with high risk of misdiagnosis. The long preclinical phase of PD provides the possibility for early therapeutic intervention once disease-modifying therapies have been developed, but lack of biomarkers for early diagnosis and monitoring of disease progression represents a major obstacle to achievement of this goal. Accordingly, research efforts aimed at identification of novel biomarkers have been increasing in the past 5 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
136
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 185 publications
(141 citation statements)
references
References 124 publications
5
136
0
Order By: Relevance
“…Most studies of CSF A β species in PD have reported slight reductions 14, 15. We and others have found a correlation between CSF A β 42 levels and memory performance in PD,15, 16 also in subjects with normal CSF A β 42 levels (thus without evidence for amyloid plaques) 15, 17.…”
Section: Introductionmentioning
confidence: 49%
“…Most studies of CSF A β species in PD have reported slight reductions 14, 15. We and others have found a correlation between CSF A β 42 levels and memory performance in PD,15, 16 also in subjects with normal CSF A β 42 levels (thus without evidence for amyloid plaques) 15, 17.…”
Section: Introductionmentioning
confidence: 49%
“…27 We previously demonstrated that actin is a target for intracellular Syn, and that wt and A30P-mutated Syn differentially modulate actin dynamics. 13 Here, we provide evidences that the extracellular accumulation of either wt or A30P Syn correlates with an unbalance of actin turnover, resulting in microfilament stabilization.…”
Section: Discussionmentioning
confidence: 99%
“…α-Synuclein is the main component of Lewy bodies, the hallmark of Parkinson's disease, and elevated wild-type α-synuclein levels and polymorphisms of the α-synuclein gene are known to be closely linked to the severity and risk of developing Parkinson's disease (Parnetti et al, 2013). Furthermore, a physical interaction between PLD2 and α-synuclein reported in vivo can inhibit PLD2 activity (Jenco et al, 1998).…”
Section: Notementioning
confidence: 99%